PANDANGAN DUNIA DALAM NOVEL SI PARASIT LAJANG KARYA AYU UTAMI: STRUKTURALISME GENETIK LUCIEN GODLMANN - Amalia, Nur Pitri; Nensilianti, Nensilianti; Faisal, Faisal (Fakultas Bahasa dan Sastra Indoensia, 2025)
This research aims to describe social humanitarian facts and the author's worldview as outlined in the novel being analyzed. This type of research is qualitative. This research data is in the form of words, sentences and paragraphs that reveal the content of the story in the novel. The data source for this research is the novel Si Parasit Lajang by Ayu Utami, which was published in 2003. The approach used is Lucien Goldmann's genetic structuralism. As a result of research on the novel Si Parasit Lajang by Ayu Utami which was used as the research object, two aspects of genetic structuralism were obtained, namely human facts about politics and culture. And we also found the author's worldview about sex, gender and marriage in the novel Si Parasit Single by Ayu Utami.